Cardiovascular syphilis: a rare case report and literature review of severe aortic regurgitation and bilateral coronary ostial stenosis - Wang, Ru; Zhang, Li; Xia, Binfeng; Kong, Min; Huang, Huihui; Yin, Xia (Frontiers in Cardiovascular Medicine, 2025)
Due to the low incidence of cardiovascular involvement in syphilis, there are currently no established consensus or guidelines for managing such cases. The patient, with no coronary artery disease risk factors, presented with chest pain and heart failure (HF). Emergency coronary angiography revealed severe stenosis of the bilateral coronary ostia, with smooth intimal lining in the remaining coronary arteries. Echocardiography showed severe aortic regurgitation. Positive syphilis serology strongly suggested cardiovascular syphilis (CVS). The patient was transferred to cardiothoracic surgery for aortic valve replacement (AVR) and coronary artery bypass grafting (CABG), but died from acute HF despite resuscitation efforts.